The man who wasn't there [videorecording (DVD)] - Coen, Ethan; Coen, Joel; Thornton, Billy Bob; McDormand, Frances; Alexi-Malle, Adam, 1964-; Jenkins, Richard, 1947-; Johansson, Scarlett, 1984-; Shalhoub, Tony, 1953-; Gandolfini, James (2002)
In a sleepy Northern California town in the 1940s, Ed Crane, a humble barber, suspects that his wife Doris is having an affair with her boss. When a stranger comes into town hinting that there is a fortune to be made in investing in the new invention of dry cleaning, Ed hatches a blackmail scheme he hopes will make him rich and get him some revenge at the same time. His plan goes horribly awry when he accidentally commits a murder for which Doris is blamed, landing her in jail, and Ed at the mercy of big-city lawyer Freddy Riedenschneider.